Pandangan Hukum Islam Terhadap Intoleransi Salafi Wahabi - Endang Madali (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2020)
Salafism-Wahhabism is intolerance in the problem of khilāfīyah. In ideological issues they are completely intolerant, and in some cases of of worship are tolerant. This research supports some of the statements from the work of Natana J. Delong-Bas through his book titled “Wahhabi Islam: From Revival and Reform to Global Jihad” (2004), Abdullahi Ahmed an-Naʻim in “Islam and Secular State: Negotiating the Future of Sharia” (2008), and Mazen Hashem through his writings titled “Contemporary Islamic Activism: The Shades of Praxis”, Sociology of Religion (2006). These scholars generally stated that Wahhabism was a radical Madhhab or doctrine or movement because it always persuades the followers to maintain the ‘pure teachings of Islam’, which believed by the proponents applicable to all Muslims. In addition, the Wahhabis have a view of puritanical Islam, which is to be intolerant in a variety of differences, so as to impose uniformity of religious understanding in Indonesia. Therefore, there is no one among them who said that the Salafi Wahabi is a moderate school of though.